ANTIBACTERIAL ACTIVITY AND TOXICITY TEST OF SPONGE EXTRACT Stylissa massa (Carter, 1887) FROM LAMPUNG WATERS - Susanti, Oktora Susanti,; Setyawan, Agus; Puspitasari, Dwi; Parabi, Achmad Reza; Sari, Azzahra Indah; Habib, Farid Alif; Hilmi, Haidar; Rahaz, Muhammad Faiz Thoyib; Maharani, Ni Putu Diva; Alfina, Ria; Gunawan, Riyan (University of Lampung, 2023)
Geographically, indonesia is natural resource countries which have large marine biodiversity, one of these is the coral reefs ecosystem. Sponge is one of any animal of the phylum porifera and a marine invertebrates that live in coral reefs ecosystem. Stylissa massa sponge can produce these secondary of metabolic processes in cells in his body. Many research stated that extracts of sponges having compound that is the sitotoksin bioaktif, anti tumor, antiviral drug, anti inflammatory and others. Stylissa massa is one species of sponge that characterizes demospongiae class, phylum porifera, and kingdom animalia. The study aimed to identify the activity of extracts antimikroba Stylissa massa on several pathogens derived from waters and land, and this study also to determine the level of toxicity Stylissa massa extract with Brine Shrim Lethality Test (BSLT). The antibacterial activity Stylissa massa extract against MDR S. aureus, MDR E.coli, Vibrio vulnivicus, Vibrio parahameolyticus, Vibrio alginoliticus, Vibrio harveyi, Salmonella thypi, Staphylococcus aureus, Escherichia coli and Aeromonas hydrophyla. The results showwed that the extract of Stylissa massa hase been created inhibition zone against all of the pathogen used. S.aureus bacteria at the smallest extract concentration (10 ppm) has created inhibition zone 8,68 mm and at the highest extract concentration (10.000 ppm) has created inhibition zone 10,83 ppm. The results of the analysis by using a graph indicating that probit LC50 extract Stylissa massa is 100 µg/mL, from the data can be concluded that extracts sponges stylissa massa have cytotoxic potential.Keyword: Sponge, Stylissa massa, extract, antibacterial, BSLT